Mobile Learning Readiness in dental students of Zanjan University of Medical Sciences in 2018-2019 - Azin Nourian (Journal of Medical Education Development, 2020)
Background: one of the most important individual factors that affect the acceptance and effectiveness of mobile learning is readiness. The aim of this study is to assess the Mobile Learning Readiness in dental students of Zanjan University of Medical Sciences in 2018-2019.